DISCOURSE ON ELECTION DISTRICT ARRANGEMENTS OF DPR RI: DISKURSUS PENGATURAN DAERAH PEMILIHAN ANGGOTA DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - Marcellino Hariadi Nugroho; Yusdiyanto Yusdiyanto; Malicia Evendia (Constitutional Law Society, 2023)
Article 187 paragraph (5) Law Number 7/2017 (Election Law) stipulates that the arrangement of the electoral districts for DPR members and the number of seats for each electoral district is determined by the legislators by attaching them in Appendix III Election Law. The existence of these provisions prompted the Non-Governmental Organization (NGO) Association for Elections and Democracy (Perludem) to submit a judicial review to the Constitutional Court. With the issuance of Constitutional Court Decision Number 80/PUU-XX/2022, the arrangements regarding electoral districts have undergone quite significant changes. This research is a normative legal research with a qualitative type. The problem approach used is the case, statutory, and comparative approach. The results of the study show that the arrangements regarding electoral districts have undergone significant changes after the issuance of the Constitutional Court Decision Number 80/PUU-XX/2022. This change can be seen from the authority to prepare and allocate seats which were previously in the hands of the legislators (through Annexes III of the Election Law) to the KPU (through KPU Regulations). In addition, several electoral arrangements in Brazil can be adopted by Indonesia, including regarding the proportional calculation method, population data, and the election management body as the institution authorized to manage electoral districts.